Pemanfaatan Media Sosial Whatsapp sebagai Sarana Penyebaran Informasi di Kantor Dinas Perpustakaan dan Arsip Kabupaten Labuhanbatu Utara - Albagani, Fauzan Reynaldi; Batubara, Abdul Karim; Yusniah, Yusniah (Asian Journal of Science, Technology, Engineering, and Art, 2023)
This research aims to determine the use of WhatsApp social media as a means of disseminating information at the North Labuhanbatu Regency Library and Archives Service Office. And it aims to determine the advantages and disadvantages of using WhatsApp social media as a means of disseminating information at the North Labuhanbatu Regency Library and Archives Service Office. The theory used in this research is New Media theory. This type of research uses qualitative methods with a descriptive approach. By using WhatsApp social media, information can be spread easily. Significant changes can be seen when the Head of Service disseminates information quickly and is easily known to other employees. It can also be seen within the group and employee activity can be seen. The advantage of using WhatsApp social media as information dissemination, it makes it easier to disseminate information between employees in disseminating information that is delivered quickly and carried out online. If there is something that must be conveyed by the Head of Service or something that is not understood, you can discuss it in the group. The weakness of using WhatsApp social media to disseminate information is that you have to have an internet connection so that the message can be conveyed immediately. Because WhatsApp is a social media application whose main function is to communicate, the dissemination of information can be fulfilled if someone spreads the information.